The effect of dietary protein intake on immune status in pigs of different genotypes - Yulong Tang (Taylor & Francis Group, 2018)
Little is known about the immune status of different pig breeds and the role of dietary protein intake. The present study, performed on 96 barrows (48 pure-bred Bama mini-pigs (fatty genotype) and 48 Landrace pigs (lean genotype)) randomly assigned to two dietary treatment groups (low- or adequate protein diet), with twenty-four24 individuals per treatment), evaluated the levels of immunoglobulins and cytokines in serum, and intestinal and splenic innate immunity on the two breeds. Data showed significant interactions between breed and diet for adaptive and innate immunity. Throughout the experiment, Landrace pigs showed significantly higher intestinal immune responses than Bama mini-pigs, and an adequate provision of dietary protein improved the expression of specific antibodies in early growth phases. These finding have important implication for improving the immune status of Landrace pigs, which are a major source of protein for humans. Abbreviations: BW: Body Weight; NRC diet: National Research Council diet; GB diet: Chinese conventional diet; CSFV: Classical Swine Fever Virus; IgG: Immunoglobulin G; IgM: Immunoglobulin M; SIgA: Secretory Immunoglobulin A.